Advances in organometallic chemistry. - Hill, Anthony F. (Advances in organometallic chemistry, 2001)
Almost all branches of chemistry and material science now interface with organometallic chemistry-the study of compounds containing carbon-metal bonds. Organometallic compounds range from species which are so reactive that they only have a transient existence at ambient temperatures to species which are thermally very stable. This widely acclaimed serial contains authoritative reviews that address all aspects of organometallic chemistry, a field which has expanded enormously since the publication of Volume 1 in 1964.